Identitas budaya Prancis dalam pertunjukan lawakan tunggal Hexagone oleh Fary - Yeremia, Edward; Andika, Yunilis; Ekowati, Sri Harini (Franconesia, 2023)
This research aims to describe the types of French cultural identity in the first part of Fary's stand up comedy show video entitled Hexagone. This research uses the main theory of Multiple Cultural Identity Types (CITs) which originates from the book Intercultural Communication: A Reader 14th Edition by Larry A. Samovar, Richard E. Porter, Edwin R. McDaniel, and Carolyn Sexton Roy (2014). There are six (6) types of cultural identities included in the Multiple Cultural Identity Types (CITs) theory, namely National and Ethnic Cultures, Sex and Gender, Profession, Geographic Area, Corporation, Physical Ability and Disability. This research uses a content analysis method which consists of three (3) stages, namely (1) Data collection by looking at words, phrases, and sentences from data sources, (2) Data classification by understanding the meaning as well as speeches from data sources and grouping words, phrases and sentences used as research data, (3) Data analysis by analyzing the data that has been found and making conclusions. The analysis technique in this research uses interactive model data analysis from Miles and Huberman with three (3) stages, namely (1) Data reduction by simplifying or narrowing data according to theory, (2) Data presentation using diagrams and narrative text on interpretation data, (3) Withdrawal of Conclusions/Verification by drawing conclusions based on the results of the research as well as answering the formulation of the problem. The results of this research indicate that there are thirty (30) speeches indicating types of French cultural identity in the first part of Fary's stand up comedy show video entitled Hexagone. The thirty (30) speeches are divided into eighteen (18) speeches on the cultural identity of the National and Ethnic Culture, seven (7) speeches on the cultural identity of the Geographic Area, two (2) speeches on the cultural identity Sex and Gender, two (2) speeches on the cultural identity of the Profession, one (1) speech on the cultural identity of the Corporation, and zero (0) speech on the cultural identity of the Physical Ability and Disability because the type of that cultural identity was not found in the data source.